2013
DOI: 10.1002/ange.201302197
|View full text |Cite
|
Sign up to set email alerts
|

Diaminodiacid‐Based Solid‐Phase Synthesis of Peptide Disulfide Bond Mimics

Abstract: Das antimikrobielle Peptid Tachyplesin I wurde als Modell für die Titelstrategie verwendet, die zur Herstellung von peptidischen Makrocyclen mit doppeltem Disulfidersatz entwickelt wurde. Die Faltung und Aktivität der Analogen von Tachyplesin I variierten abhängig von den Disulfidsurrogaten. SPPS=Festphasenpeptidsynthese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 53 publications
(7 reference statements)
0
17
0
Order By: Relevance
“…Diaminodicarboxylic acid (DADC) building blocks x , y , and z (Figure A) were synthesized according to literature and used for the synthesis of analogs 15 to 17 as described before . Exemplarily, the synthesis strategy for thioether analog 16 (u 16 , Cys 21 ) is shown in Figure D.…”
Section: Resultsmentioning
confidence: 99%
“…Diaminodicarboxylic acid (DADC) building blocks x , y , and z (Figure A) were synthesized according to literature and used for the synthesis of analogs 15 to 17 as described before . Exemplarily, the synthesis strategy for thioether analog 16 (u 16 , Cys 21 ) is shown in Figure D.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme , the first Phe residue was anchored to 2‐chlorotrityl chloride resin with Fmoc‐Phe‐OH in the presence of DIPEA. Next, the glycopeptides were assembled via sequential introduction of Fmoc‐Pro‐OH, Fmoc‐ d ‐Phe‐OH, Fmoc‐Leu‐OH, Fmoc‐Orn(Boc)‐OH, Fmoc‐Val‐OH, Fmoc‐Tyr(tBu)‐OH, Fmoc‐Gln(Trt)‐OH, building blocks 3a–4f , and Fmoc‐ d ‐Phe‐OH using 20% piperidine as Fmoc‐removed reagents and HCTU(N,N,N',N'‐Tetramethyl‐O‐(6‐chloro‐1H‐benzotriazol‐1‐yl)uronium hexafluorophosphate)/DIPEA in coupling reactions . Subsequently, the loaded resins were treated with AcOH/TFE/dichloromethane (DCM) (1 : 1 : 8) to give the linear glycopeptides 9a–f and 10a–f .…”
Section: Chemistrymentioning
confidence: 99%
“…[8] One possible alternative strategy is based on pre-made diaminodiacid building blocks, which incorporate the disulfide surrogate and are included in the assembly of the peptide through SPPS ( Figure 2). [9,10] In pioneering studies, the Vederas and van der Donk groups demonstrated the use of DADA strategy in synthesis of naturally occuring lantibiotics. [10] A series of DADA building blocks have also been developed and incorporated into various peptides.…”
Section: Introductionmentioning
confidence: 99%
“…[10] A series of DADA building blocks have also been developed and incorporated into various peptides. [9][10] This review summarizes the development of the DADA strategy for the synthesis of disulfide surrogate peptides. We describe the principle of the DADA strategy, the development of DADA building blocks, and the effect of DADA replacement on peptide structures and activities.…”
Section: Introductionmentioning
confidence: 99%